Meeting: François Houtart “the common good of the common property of Mankind” - François Houtart (Revista Kavilando, 2016)
This article relates the transcript of the conference Hourtart Francois offered in the city of Medellin Colombia, in 2015 developed the theme was: “In the commons, at the common good of humanity